Sustainable Tourism Development Strategy Through the Community-Based Tourism Model at DTW Pesona Leuweung Oko, Cirapuhan Village, Garut District - Kurniadinata, Widya; Suhartini, Ninik (GoAcademica Research & Publishing, 2024)
Community-based tourism (CBT) is very important for tourism growth, especially to support the economy of communities around tourist destination areas (DTW). Garut Regency, with its natural resources, culture and natural beauty, has great potential in this region. However, the growth of the tourism sector must be adjusted to the principles of sustainability and consider the prosperity of local communities. CBT is a tourism development approach that involves local communities to actively participate in planning, managing and benefiting from the tourism industry. This gives communities the opportunity to control the progress of tourism in their region. In Cirapuhan, especially in DTW Leuweung Oko, the process of developing Tourism Villages faces challenges. During the development process of the Leuweung Oko DTW, there was a disagreement between the developer and the surrounding community because this instrument was needed to look deeper at the source of the problem, using this qualitative descriptive method to explain tourism conditions clearly. The results of this research are problems that occur between tourism actors in Pesona Leuweung OKO, causing losses for each actor.